RANCANG BANGUN E-LEARNIG PADA SMPS KATOLIK MATER INVIOLATA LARANTUKA BERBASIS WEBSITE - Riberu, Hendrikus S. E. (STIKOM Uyelindo Kupang, 2022)
The learning process at the Mater Inviolata Larantuka Catholic Junior High School using conventional or face-to-face methods was disrupted due to the Covid-19 pandemic that hit Indonesia, learning at the Mater Inviolata Larantuka Catholic Junior High School which was originally conventional, namely teachers and students carried out the teaching and learning process directly in the classroom. forced to carry out online, namely students learning and teaching teachers must continue even though students are at home. The purpose of this research is to design and build a website e-learning as a medium for student learning. The research methods used in this research are interviews, literature study, observation and questionnaires. Making this application using Adobe Dreamweaver and database. The expected result in making e-learning is to facilitate the learning and teaching process between teachers and students in online. It is hoped that this e-learning can help improve teaching and learning activities at Mater Inviolata Catholic Middle School Larantuka